A Literature Review of King Abdullah II Center Standard in Health Care Sector in Jordan - Fauzilah, Salleh; Anas, Al-Mhasnah; Lara Younes, Al- Deabes (2018)
: Framework: This study came to evaluate the effects of KAIIA standards, especially processes and Services sub-standard (Service Procedures, Service Time, Service fees, Employees attitude, Suggestions and complaints, Infrastructure, and Website services) on customer satisfaction. Methodology: This study comes to investigate the impact of applying KAIIA model on patients' satisfaction among Jordanian health sector. The KAIIA survey adopted and used toward one of the Jordanian royal medical hospitals which applying KAIIA model. SPSS (21) was used to test and investigate the hypothesis among the dimensions and their items. Results: The results of applying excellence model in Jordan could be motivated by: Improving and developing procedures, meeting patient needs, fees of service provided, and customer satisfaction.